The Implementation of the Merdeka Curriculum and Academic Supervision on the Quality of Learning in Elementary Schools - Juni Astuti; Reva Maria Valianti; Aswadi Jaya (Yayasan Sembilan Pemuda Indonesia, 2027)
Muara Telang District, characterized by its unique water-surrounded geographical features, faces numerous educational challenges such as limited infrastructure, uneven teacher competency development, and suboptimal academic supervision. These issues highlight the need for a comprehensive study examining the influence of Merdeka Curriculum implementation and academic supervision on the quality of learning in elementary schools. The purpose of this study is to comprehensively analyze and describe the influence of the implementation of the Merdeka Curriculum and academic supervision on the quality of learning in Elementary Schools in Muara Telang District. This quantitative survey research involved 84 teachers selected through proportional random sampling. Data were collected using questionnaires and analyzed with SPSS version 26. The statistical tests included validity and reliability assessments, descriptive statistics, simple and multiple regression analyses, t-tests, F-tests, and coefficient of determination. The findings revealed that all three variables, implementation of the Merdeka Curriculum, academic supervision, and learning quality, were categorized as “good,” with mean scores of 120.04, 121.57, and 120.71, respectively. Hypothesis testing demonstrated significant partial and simultaneous effects of both independent variables on learning quality. The coefficient of determination (R²) of 0.68 indicated that 68% of the variance in learning quality could be explained by the two variables, while the remaining 32% was influenced by other external factors. This study underscores that sustainable improvement in learning quality can only be realized through consistent implementation of the Merdeka Curriculum supported by systematic and well-structured academic supervision focused on enhancing teachers’ professionalism.